(untitled) (Annual of the Faculty of Philosophy in Skopje, 2016)
The text offers an overview of the categories of space and time through the sacred-profane dichotomy and the characteristics of the belief in the sacred in Mircea Eli- ade ’s theory. Sacred space is more important than the profane one, it is heterogeneous - entering it entails a temporary inhabiting of a sphere of a superior ontological status. Emplacement in the world for the primordial as well as for the contemporary believer is thanks to the orientation having the sacred as a centre, an axis (hence, the beliefs in the axis of the world and the symbolism of the centre), something that guarantees a safe environment and creates cosmos. Myths as sacred tales refer to cosmogony which implies topogony, and with their sacredness and performative powers tend to reactualise the condition of the initial extériorisation of the sacred, of the actions of the sacred ancestors or deities. Therefore, any subsequent emplacement is mimesis of the initial differentiation and structuring of the elements in the world. The reactualisation of cosmogony, apart from this, includes a return to the sacred time of the Beginning. Sacred time is as non-homogenous as space is, and the religious referring to the sacredness of “that time ” (as Eliade employs it) means to cease the profane duration and introduce a time which does not pass, and which has the ability to restore the reality of the religious man.